Cluster randomized controlled trial testing the effectiveness of a self‐management intervention using the teach‐back method for people with heart failure. (12th June 2019) - Dinh, Ha T. T.; Bonner, Ann; Ramsbotham, Joanne; Clark, Robyn
Abstract: In this study, we examined the effectiveness of a self‐management intervention delivered to people with heart failure in Vietnam. It used teach‐back, a cyclical method of teaching content, checking comprehension, and re‐teaching to improve understanding. A single‐site cluster randomized controlled trial was conducted, and six hospital wards were randomized into two study groups. On the basis of ward allocation, 140 participants received either usual care or the teach‐back heart failure self‐management intervention plus usual care. The intervention involved, prior to discharge, an individual educational session on heart failure self‐care, with understanding reinforced using teach‐back, a heart failure booklet, weighing scales, diary, and a follow‐up phone call 2 weeks post‐discharge. The control group received usual care and the booklet. Outcomes were heart failure knowledge, self‐care (maintenance, management and confidence), and all‐cause hospitalizations assessed at 1 and 3 months (end‐point). Upon completion of the study, the intervention group had significantly greater knowledge and self‐care maintenance than the control group. Other outcomes did not differ between the two groups. The teach‐back self‐management intervention demonstrated promising benefits in promoting self‐care for heart failure patients.